Distributed, ambient and pervasive interactions : 5th International Conference, DAPI 2017, held as part of HCI International 2017, Vancouver, BC, Canada, July 9-14, 2017, proceedings /: 5th International Conference, DAPI 2017, held as part of HCI International 2017, Vancouver, BC, Canada, July 9-14, 2017, proceedings. (2020) - Unknown
No abstract available